Design of Public Space at Roundout Old City Pulo Brayan, Medan with Sustainable Architecture Approach - Robby Pratama; Melly Andriana; Dara Wisdianti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The development of major cities in Indonesia, including Medan, is inseparable from complex social, economic, and political dynamics. This transformation often leads to a mismatch between the city's image and its local identity, reduced access to adequate housing, and the decline of public open spaces, particularly in urban fringe areas such as Pulo Brayan. In fact, public spaces play a crucial role in supporting social interaction and ecological functions within a city. This study focuses on the importance of redesigning public space in the Pulo Brayan area using a sustainable architectural approach. The main objective is to create a public space that can address social, economic, and environmental challenges in an integrated manner. The proposed design emphasizes the integration of historical values, active community participation, and ecological functionality to support the realization of sustainable cities, in line with the principles of Sustainable Cities and Communities. Thus, this design is expected to serve as a contextual, inclusive, and sustainable model for public space regeneration.